Nitrogen‐Doped Graphene Nanoscroll Foam with High Diffusion Rate and Binding Affinity for Removal of Organic Pollutants. Issue 14 (1st February 2017) - Fang, Qile; Zhou, Xufeng; Deng, Wei; Liu, Yuewen; Zheng, Zhi; Liu, Zhaoping
Abstract : A nitrogen‐doped 3D graphene foam assembled with nanoscroll structure is constructed via a facile mild‐heating methodology using a polar molecule of formamide as the driving regent. The as‐prepared graphene nanoscroll foam exhibits promising performance in organic pollutant removal with improved adsorption rate and high binding affinity, and is thought to be a novel adsorption material.